ANÃLISES DE MEL DE Apis mellifera L., 1758 E Tetragonisca angustula (LATREILLE, 1811) COLETADO EM PIRACICABA-SP - Rodrigues, AndrÃ©a C. L.; Marchini, Luis Carlos; Carvalho, Carlos Alfredo L. de (REVISTA DE AGRICULTURA, 2015)
ANÃLISES DE MEL DE Apis mellifera L., 1758 E Tetragonisca angustula (LATREILLE, 1811) COLETADO EM PIRACICABA-SP